Exploring the Genome and Phenotype of Multi-Drug Resistant Klebsiella pneumoniae of Clinical Origin - Anes, João; Hurley, Daniel; Martins, Marta; Fanning, Séamus (Frontiers in Microbiology, 2017)
Klebsiella pneumoniae is an important nosocomial pathogen with an extraordinary resistant phenotype due to a combination of acquired resistant-elements and efflux mechanisms. In this study a detailed molecular characterisation of eleven Klebsiella pneumoniae isolates of clinical origin was carried out. Eleven clinical isolates were tested for their susceptibilities, by disk diffusion and broth microdilution and interpreted according to CLSI guidelines. Efflux activity was determined by measuring the extrusion of ethidium bromide and biofilm formation was assessed following static growth in Müeller-Hinton and minimal media M9 broths at two temperatures and time points. Template DNA from all eleven isolates was extracted and sequenced. The study collection was found to be resistant to several (extended-spectrum beta-lactam) ESBL-type compounds along with several (fluoro)quinolones (FQ). Resistance to tetracycline accounted for 55% of the study collection (n=6) and three of the 11 isolates were resistance to carbapenems. Genotyping identified blaCTX-M-15 (82%), blaSHV-12 (55%) and blaTEM-1B (45%) ESBL encoding genes and FQ resistance was associated the presence of the oqxAB operon, identified in 10 of the 11 isolates and qnrB gene in one isolate. The polymorphisms detected in the quinolone resistance-determining regions (QRDRs) were associated with isolates of the clonal group CG15. Sequence types (ST) identified were representative of previously described clonal groups including CG258 (n=7), CG15 (n=3) and CG147 (n=1). Plasmid replicon type databases were queried indicating the presence of IncFII and IncFIB replicon types in the majority of the isolates (91%), followed by IncFIA (45%), and IncR (45%). Two of the 11 isolates were found positive for yersiniabactin siderophore-encoding genes. No differences in the ability to efflux ethidium bromide were identified. Biofilm formation was stronger when the isolates were grown under stressed conditions at 37˚C for a period up to 96 hours. These data confirm the fact that well recognised clonal groups of Klebsiella pneumoniae of importance to human health carries a diverse repertoire of antimicrobial resistance determinants, particularly related to critically important drugs in the ESBL and FQ classes. The capacity of most isolates to form strong biofilms, when stressed under laboratory-simulated conditions, supports the risk to human health associated with nosocomial infections